Penerapan Konsep Pluralisme Hukum Sally Falk Moore dalam Penyelesaian Konflik di Tingkat Pemerintahan Daerah - Turmudzi, Khoiru (Jurnal Hukum Caraka Justitia, 2025)
This article discusses the application of Sally Falk Moore's concept of legal pluralism in conflict resolution at the local government level in Indonesia, known for its cultural diversity and complex normative systems. Legal pluralism refers to the coexistence of various legal systems, where customary law and state law interact and influence each other. In this context, the article explains how customary law is recognized within Indonesia's positive legal framework and its important role in resolving disputes arising from differences between the two legal systems. Through an analysis of the interaction between state law and customary law, the article shows that applying legal pluralism can create balance and justice in conflict resolution, and strengthen the identity and rights of indigenous peoples. Using the concept of a semi-autonomous social environment, this article highlights the importance of recognizing the existence of customary law in improving social order and protecting community rights. In conclusion, applying legal pluralism not only provides solutions to conflicts but also contributes to developing a harmonious and equitable society.